1994
DOI: 10.1001/archsurg.1994.01420310044007
|View full text |Cite
|
Sign up to set email alerts
|

The Malignant Transformation of Liver Cell Adenomas

Abstract: Malignant transformation of a liver cell adenoma is a rare phenomenon, but it does occur. Alpha-fetoprotein levels may be more helpful in diagnosis than expected from previous reports. Solitary benign adenomas should be resected whenever possible. Patients with diffuse multiple tumors should be observed closely over a long period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
90
0
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(94 citation statements)
references
References 17 publications
1
90
0
3
Order By: Relevance
“…In this series, 3/17 (18%) of hepatic adenomas showed the presence of carcinoma. By comparison, Foster and Berman 17 reported a 13% frequency of malignancy in 39 adenomas, whereas Closset et al 16 reported a frequency of 1/16 (6%) of adenomas with co-existing cancer and 2/16 (12%) with dysplasia. ZucmanRossi, in a multicenter study, found 5/93 (5%) of hepatic adenomas with malignant degeneration and 6/93 (6%) cases borderline for hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 96%
“…In this series, 3/17 (18%) of hepatic adenomas showed the presence of carcinoma. By comparison, Foster and Berman 17 reported a 13% frequency of malignancy in 39 adenomas, whereas Closset et al 16 reported a frequency of 1/16 (6%) of adenomas with co-existing cancer and 2/16 (12%) with dysplasia. ZucmanRossi, in a multicenter study, found 5/93 (5%) of hepatic adenomas with malignant degeneration and 6/93 (6%) cases borderline for hepatocellular carcinoma.…”
Section: Discussionmentioning
confidence: 96%
“…To our knowledge, only one case of malignant transformation among patients with adenomatosis 4 and nine cases among patients with hepatic adenoma have been reported. 8,[30][31][32][33][34][35][36][37] Among 17 patients in the literature with LA in whom follow-up was available (mean follow-up, 30.8 months), 3 developed new benign lesions [27][28][29] and 1 developed HCC 4 ; however, in those reports, the follow-up was very short and imaging studies were not performed routinely during the follow-up period. Therefore, the true rate of appearance of new lesions is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…22 In one series of 39 cases of unresected liver adenoma, 5 cases subsequently developed hepatocellular carcinoma. 23 Sometimes, hepatic adenoma is difficult to differentiate from well -differential hepatocellular carcinoma. Therefore surgery should be indicated when clinical diagnosis of hepatocellular carcinoma can't be ruled out or malignant transformation is suspected.…”
Section: Discussionmentioning
confidence: 99%